Sociodemographic and psychosocial factors associated with vaccine hesitancy - results from a longitudinal study in Singapore - Mythily Subramaniam; Edimansyah Abdin; Saleha Shafie; Shazana Shahwan; Yunjue Zhang; Pratika Satghare; Fiona Devi; Phyllis Lun; Mihael Yuxuan Ni; Siow Ann Chong (Taylor & Francis Group, 2023)
Singapore has one of the highest COVID-19 vaccination rates, however identifying vaccine-hesitant sub-groups and their concerns is vital given the need for future boosters in vulnerable populations. Furthermore, vaccine hesitancy remains a concern in the event of an emergence of a newer strain that necessitates the rolling out of a new vaccination programme. The aims of this study were to establish the extent of COVID-19 vaccine hesitancy and the factors influencing it among adults in Singapore using the Vaccine Hesitancy Scale (VHS). The study used a longitudinal methodology and participants were recruited in two waves from May 2020 to Sep 2022. In all 858 participants agreed to participate in both waves of the study. The two-factor structure of the VHS scale as established in earlier studies was tested using confirmatory factor analysis. The results revealed a two-factor structure of VHS comprising "lack of confidence" and "risks". Those who had higher stress, resilience, and concerns that they might be infected with COVID-19 at wave 1 were significantly associated with lower 'lack of confidence' scores i.e. lower vaccine hesitancy. In comparison, those with higher concerns about inadequate government preventive measures and unemployment at wave 1 were significantly associated with higher 'lack of confidence' scores. Those with higher concerns about inadequate government preventive measures in wave 1 were significantly associated with higher 'risks' scores i.e. higher vaccine hesitancy. The findings point toward the need for a nuanced messaging that considers the fears expressed by the populace and addresses them directly using clear simple language.